1990
DOI: 10.1021/j100372a023
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Hund's rule for first-row hydrides AH (A = lithium, boron, nitrogen, fluorine)

Abstract: Configuration interaction calculations have been carried out for low-lying singlet and triplet states of ('•3 +), BH(UII), (1 11 ,3 "), and FH(UII), with the aim of evaluating singlet-triplet energy component differences. These calculations represent the first systematic study of the quantum mechanical interpretation of Hund's rule in a series of molecules. While early molecular work on Hund's rule suggested that the electron-nuclear attraction may always be deeper in the triplet than in the singlet, exception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The potential energy functions for various electronic states of BH were determined using the valence full configuration interaction approach by Gagliardi et al [24] and using the multireference configuration interaction approach with large correlation-consistent basis sets by Petsalakis and Theodorakopoulos [33] and by Miliordos and Mavridis. [34] In the latter work, the values of D e , r e , and m were predicted for the ground electronic state of BH to be 29 660 cm 21 , 1.230 Å , and 2261 cm 21 , respectively. The higher-order electron correlation effects on properties of BH were investigated by Halkier et al, [28] Larsen et al, [29] Abrams and Sherrill, [30] and Temelso et al [32] Previous theoretical predictions of the spectroscopic constants for the X 1 R 1 state of BH were recently reviewed by Sinha Mahapatra et al [36] The accurate binding energy D e for the X 1 R 1 state of BH is still not known experimentally.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The potential energy functions for various electronic states of BH were determined using the valence full configuration interaction approach by Gagliardi et al [24] and using the multireference configuration interaction approach with large correlation-consistent basis sets by Petsalakis and Theodorakopoulos [33] and by Miliordos and Mavridis. [34] In the latter work, the values of D e , r e , and m were predicted for the ground electronic state of BH to be 29 660 cm 21 , 1.230 Å , and 2261 cm 21 , respectively. The higher-order electron correlation effects on properties of BH were investigated by Halkier et al, [28] Larsen et al, [29] Abrams and Sherrill, [30] and Temelso et al [32] Previous theoretical predictions of the spectroscopic constants for the X 1 R 1 state of BH were recently reviewed by Sinha Mahapatra et al [36] The accurate binding energy D e for the X 1 R 1 state of BH is still not known experimentally.…”
Section: Introductionmentioning
confidence: 88%
“…In the calculation at the Hartree-Fock level of theory by Cade and Huo, [11] the potential energy function of BH in its X 1 R 1 electronic state was determined. The binding energy D e , the equilibrium internuclear distance r e , and the vibrational fundamental wavenumber m were calculated to be 22 500 cm 21 , 1.220 Å , and 2401 cm 21 , respectively. The electron correlation effects of BH were then discussed by several authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12,13] The origin of Hund's multiplicity rule for heavier atoms has mostly been examined at the HF level. It is interesting to study the origin of Hund's multiplicity rule in heavier atoms beyond the HF level.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have studied Hund's rule for atoms [8][9][10][11][12][13][14][15][16][17][18][19] and light molecules [20][21][22][23][24][25][26][27][28] by Hartree-Fock (HF) and other variational calculations. They have found that the stabilization of the highest multiplicity state relative to the lower multiplicity states is ascribed to a lowering in V en that is gained at the cost of increasing V ee as well as T. Davidson 8,9) has first pointed out that V ee is larger for the triplet than for the singlet by HF calculations for low-lying excited states of the helium atom.…”
Section: Introductionmentioning
confidence: 99%